Chemical signaling in the developing avian retina: Focus on cyclic AMP and AKT-dependent pathways - Duarte-Silva, A. T.; Ximenes, L. G. R.; Guimarães-Souza, M.; Domith, I.; Paes-de-Carvalho, R. (Frontiers in Cell and Developmental Biology, 2022)
Communication between developing progenitor cells as well as differentiated neurons and glial cells in the nervous system is made through direct cell contacts and chemical signaling mediated by different molecules. Several of these substances are synthesized and released by developing cells and play roles since early stages of Central Nervous System development. The chicken retina is a very suitable model for neurochemical studies, including the study of regulation of signaling pathways during development. Among advantages of the model are its very well-known histogenesis, the presence of most neurotransmitter systems found in the brain and the possibility to make cultures of neurons and/or glial cells where many neurochemical functions develop in a similar way than in the intact embryonic tissue. In the chicken retina, some neurotransmitters or neuromodulators as dopamine, adenosine, and others are coupled to cyclic AMP production or adenylyl cyclase inhibition since early stages of development. Other substances as vitamin C and nitric oxide are linked to the major neurotransmitter glutamate and AKT metabolism. All these different systems regulate signaling pathways, including PKA, PKG, SRC, AKT and ERK, and the activation of the transcription factor CREB. Dopamine and adenosine stimulate cAMP accumulation in the chick embryo retina through activation of D1 and A2a receptors, respectively, but the onset of dopamine stimulation is much earlier than that of adenosine. However, adenosine can inhibit adenylyl cyclase and modulate dopamine-dependent cAMP increase since early developmental stages through A1 receptors. Dopamine stimulates different PKA as well as EPAC downstream pathways both in intact tissue and in culture as the CSK-SRC pathway modulating glutamate NMDA receptors as well as vitamin C release and CREB phosphorylation. By the other hand, glutamate modulates nitric oxide production and AKT activation in cultured retinal cells and this pathway controls neuronal survival in retina. Glutamate and adenosine stimulate the release of vitamin C and this vitamin regulates the transport of glutamate, activation of NMDA receptors and AKT phosphorylation in cultured retinal cells. In the present review we will focus on these reciprocal interactions between neurotransmitters or neuromodulators and different signaling pathways during retinal development.